If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5 + -7x = -15 Reorder the terms: 5 + 4x + -7x = -15 Combine like terms: 4x + -7x = -3x 5 + -3x = -15 Solving 5 + -3x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = -15 + -5 -3x = -15 + -5 Combine like terms: -15 + -5 = -20 -3x = -20 Divide each side by '-3'. x = 6.666666667 Simplifying x = 6.666666667
| 50=3x-12x+1 | | 10x^2+3x+9=13 | | X^2-6x-11=-4 | | x*6+86=x*10-6 | | f(x)=9xsquared+5x+1 | | 2[x+8]=-4[5x-2]+8x | | 2x-7+4x+15=56 | | (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x |